Peningkatan kompetensi kewirausahaan melalui program pengembangan produk unggulan daerah kain khas daerah Palembang - Bainil Yulina; Evada Dewata; Anggeraini Oktarida; Pridson Mandiangan; Nurul Aryanti; Welly Ardiansyah (Unri Conference Series: Community Engagement, 2020)
Entrepreneurial competence is a fundamental factor possessed by someone who has more abilities, which makes him different from someone who has average abilities. Entrepreneurial competence is an individual characteristic which includes attitudes and habits, where entrepreneurs can achieve and maintain business success. KUBE Griya Kain Tuan Kentang is located in the Tuan Kentang 4 area of Ulu Palembang and houses 25 Palembang-style cloth craftsmen. Weaving fabrics and batik with a unique special pattern. These are increasingly popular and are known to be used as materials for fashion designs for clothing, accessories for necklaces and bags. Moreover, the Palembang local government made the woven cloth a mandatory garment for official uniforms on Fridays and special days. This condition provides a great opportunity for KUBE to improve the quality of its production to foreign countries The problem with Kube Griya Kain Tuan Kentang has human resources with limited competence, is not able to speak English actively, knowledge of bookkeeping and preparation of financial reports as well as knowledge and application of taxes on business activities Palembang woven fabrics. The Regional Superior Product Development Program for Palembang's unique woven fabrics is an activity of implementing science and technology from the Sriwijaya State Polytechnic funded through the Director General of Higher Education as an effort to develop the cultural assets of the Palembang area in the form of tajung, blongsong and jupri woven fabrics. This activity aims to spur and develop superior woven fabrics typical of the Palembang region as an effort to improve quality, product quantity, distribution and marketing. To improve entrepreneurship competence, practical English language training was held, Financial Report Preparation, Selling Price Calculation and Determination, Calculation and Determination of Sales Tax for Kube Administrators and MSME Owners The method of implementation is carried out by disseminating activities, holding scheduled training in accordance with the agreement and mentoring activities, to see the success of the activity an evaluation is held by means of monitoring and distributing questions. The resulting output is in the form of increased knowledge for administrators and managers, in other words the Entrepreneurship Competence of Human Resources of Kube Griya Tuan Kentang has increased by 45%.